The international law on Indigenous Peoples in territorial organization and economic development plans - Ibañez Sánchez, Miguel (2015)
The situation of indigenous peoples has been largely documented in Peruvian history and has been linked to the dispossession of their lands, territories and natural resources. The extractive model of economic growth has increased the mining, forestry activities and the production of oil, in the territories of indigenous peoples. In addition, the territorial management, the ecological zoning, and the incentives to private investment, constantly excludes indigenous peoples threatening their survival because of territories reduction. This study compiled and analyzed part of national and international legislation of the rights of indigenous peoples, especially those living in voluntary isolation and initial contact. The laws of territorial and environmental management such as devices for economic development demonstrate the violation of international treaties relating to the rights of indigenous peoples.